Vertical bone regeneration with a simultaneous dental implant in the aesthetic zone - Jiménez Castellanos, Fabio Andrés (2022)
Introduction: Bone defects hinder implant positioning. Vertical bone deficiency is the most challenging clinical treatment due to the technique's high sensitivity and frequent Intra and postoperative complications. Alternative therapy for vertical defects is guided bone regeneration with simultaneous implantation; however, few studies have evaluated its effectiveness over time. Objective: To evaluate peri-implant tissue stability in a dental implant simultaneouslypositioned in an aesthetic zone of an area of zone vertical bone regeneration 3 years after functional load. Case Presentation: A 62-year-old male presented with the absence of the right lateral incisor and a vertical bone defect of 3mm. His initial condition affected the relation of zenith points, causing disharmony. After case evaluation, vertical guided bone regeneration and simultaneous dental implants were performed to obtain a vertical bone gain of 3mm. The implant was rehabilitated with a zirconium crown and evaluated 3 years after functional loading. Conclusion: Vertical guided bone regeneration and simultaneous dental implant in the aesthetic zone in minor bone defects (<4 mm) is an appropriate surgical and prosthetic technique to reduce surgical time, providing stability of peri-implant tissues even 3 years after functional implant loading.